Reputation: 1
After solving the recurrence relation T(n) = 3T(n/3) + nlogn
I get following equation: T(n)=3kT(n/3k)+ nlogn + nlog(n/3) + nlog(n/3^2) …nlog(n/3^k)
How can I simplify the summation and how to know the asymptotic function?
Upvotes: 0
Views: 105
Reputation: 219
log a + log b = log(a*b)
, so something like
T(n) = 3kT(n/3k) + n^k*logn(\Pi_k(n/(3^k)))
product of 1/(3^k) (\Pi_k(1/(3^k))
) is
3^(-1/2k(k+1))
so
it simplifies
the logs become the single term n*log{3^(-1/2k(k+1)) * n^(k+1)}
that takes care of the simplification i gues..
Upvotes: 0